Tác động của chánh niệm đối với công việc và chất lượng cuộc sống của các lập trình viên ngành công nghệ thông tin - Nguyễn Minh, Thạch; Mai Thị Mỹ, Quyên; Lê Nguyễn, Hậu (JOURNAL OF ASIAN BUSINESS AND ECONOMIC STUDIES, 2021)
In the contemporary industrialized age, numerous employees including developers in the IT sector suffer from job stress regularly which may negate their job performance and consequently lead to a high turnover rate. Additionally, experiencing job stress over a long time also affects their quality of life. This study examines the impact of mindfulness as an employees’ psychological resource on their work and life. The analysis of data collected from 200 IT developers reveals that employee mindfulness significantly reduces job stress and facilitates job satisfaction. Mindfulness indirectly reduces the level of work interference with life leading to the increased quality of life. These results elucidate the mechanism in which mindfulness impacts employees’ work and life. Moreover, managers should consider mindfulness training as a measure to reduce employees’ job stress.
Keywords: Mindfulness; Job stress; Work interference with life; Job satisfaction; Quality of life; Developers